Identification of novel regulators of protein synthesis fidelity using high content genetic screens - Tavares, Joana Formigal (2020)
Protein synthesis is central to life and is being intensively studied at various levels. The exception is mRNA translational fidelity whose study has been hampered by technical difficulties in detecting amino acid misincorporations in proteins. Few genes have so far been associated to the control of protein synthesis fidelity and it is unclear how many genes control this biological process. We investigated the role of RNA modification by RNA modifying enzymes (RNAmods) in protein synthesis efficiency and accuracy. Our hypothesis was that RNAmods that modify tRNA nucleosides (tRNAmods) have a significant impact on protein synthesis through modulation of codonanticodon interactions. To address this issue, we focused our work on tRNAmods involved in the modification of tRNA anticodons. The biology of these enzymes is still poorly understood, but they are involved in RNA processing, stability and function and their deregulation is associated with cancer, neurodegenerative, metabolic and other diseases. We have set up a yeast genetic screen and used mass-spectrometry methods to determine the role of tRNAmods on proteome homeostasis. Our work identified a subgroup of yeast tRNAmods that play essential roles in protein synthesis fidelity and folding. The genes that encode insoluble proteins isolated from yeast cells lacking U34 modification were enriched in codon sites that are decoded by the hypomodified tRNAs. These aggregated proteins also participate in specific biological processes, suggesting that tRNAmods are linked to specific physiological pathways. Interestingly, we detected amino acid misincorporations at the codon sites decoded by the anticodons of the hypomodified tRNAs, demonstrating that tRNA U34 modifications control translational error rate.